Make Your Own Luck: The Wage Gains from Starting College in a Bad Economy - Alena Bicakova; Guido Matias Cortes; Jacopo Mazza (Institute of Labor Economics (IZA), 2023)
Using data for nearly 40 cohorts of American college graduates and exploiting regional variation in economic conditions, we show robust evidence of a positive relationship between the unemployment rate at the time of college enrollment and subsequent annual earnings, particularly for women. This positive relationship is not driven by selection into employment or by economic conditions at the time of labor market entry. It also cannot be explained by differential sorting into college majors or post-graduate education. Up to one third of the effect is accounted for by sorting towards more remunerative locations. The results are consistent with a behavioral change that induces individuals who experience bad economic times at the beginning of their studies to exert more effort toward obtaining higher paying jobs.
Keywords: I23; J24; J31; E32; 330; business cycle; higher education; cohort effects